Raya and The Last Dragon : Representation of Southeast Asian Culture in Film - Isma Fathanah; Luthfi Mustika Framesthia; Rabi’ah Al-Adawiyah; Silmy Shabrina Mujahadah; Mira Pitriani (Cinematology: Journal Anthology of Film and Television Studies, 2022)
Each country has a different culture with its own uniqueness. Each country also has its own way of maintaining its culture, either through education, festivals, formal or informal education, etc. However, in practice many countries have difficulties. Therefore, several countries maintain their culture through one of the arts fields, one of which is the film Raya The Last Dragon. Film Raya and The Last Dragon is a film produced by Walt Disney Animation Studios. The film was directed by Don Hall and Calos Lopes Estrada and the screenplay was written by Qui Nguyen and Adele Lim. This film tells the story of a female warrior named Raya who lives with animals as well as a means of transportation named Tuktuk in a prosperous  land, until finally becoming a dystopia world. In this film there are scenes that show several cultures in Southeast Asia. Thus, researchers are interested in re-representing and describing the culture of Southeast Asia to be conveyed in the film. This study uses a descriptive qualitative method, based on the philosophy of postpositivism, which is used to examine the condition of natural objects. From the results of this study, researchers can conclude that the film Raya and The Last Dragon presents the country of Kumandra which characterizes cultures in Southeast Asia. The purpose of this film is to show unity in differences, accept each other and coexist in many differences.